Comparison of dermatoglyphic traits and dental anomalies associated with cleft lip or cleft lip and palate patients with normal healthy children - Neha Maheshwari; Kalpana Bansal; Dayashankar J. K. Rao; Radhika Chopra (Wolters Kluwer Medknow Publications, 2013)
Background: Dermatoglyphics are considered as a window of congenital abnormalities and is known to be one of the best available diagnostic tools in genetic disorders. Objective: The present study was conducted to observe and compare the differences in the dermatoglyphic patterns between cleft lip/palate (CL/P) and normal healthy children and evaluate their associated dental findings. Setting: This is a cross-sectional prevalence study in which dermatoglyphic patterns and dental anomalies of 90 (CL/P) and normal healthy children aged 0-15 years were recorded under standard conditions of seating and lighting. Materials and Methods: Dermatoglyphic traits were recorded using ink stamp pad method. Dental findings were recorded through clinical and radiographic examination. Results: The most frequently seen dermatoglyphic trait in the study and control group was loops followed by whorls and arches. A highly significant (P < 0.001) difference between loops in the study and control group and statistically significant difference in the whorls (P = 0.001) were found using Student's t-test. The comparison of dental anomalies was accomplished using Chi-square test and hypodontia (50%) was seen maximum in cleft patients. Conclusion: Any deviation in dermatoglyphics features indicates a genetic etiology.